Dispute Resolution In Online Sales And Purchase Agreements On E-Commerce Shopee - Afrina, Dhea Nur; Siregar, Hamdan Azhar (Journal of Law, Politic and Humanities, 2025)
This research aims to analyze dispute resolution in online sales agreements, focusing on a case study of PT Shopee Indonesia. In an increasingly digital era, online transactions have become an integral part of daily life, making it essential to understand effective and fair dispute resolution mechanisms. The methodology employed in this study is a qualitative approach with descriptive analysis, involving the collection of primary data through interviews and observations, as well as secondary data from relevant literature. From the analysis conducted, it is recommended that online sales agreements be drafted more clearly, dispute resolution mechanisms be improved to enhance efficiency, and the implementation of consumer protection laws be strengthened. With these measures, it is hoped that a fairer and more satisfying e-commerce environment can be created for all parties involved. The findings indicate that online sales agreements possess a sufficiently strong legal standing; however, there are still several provisions that require clarification to ensure fairness for all parties involved. The existing dispute resolution mechanisms, while adequate, face challenges in terms of efficiency and transparency. This research also highlights the importance of consumer protection law in safeguarding consumer rights in online transactions